Wide-acceptance measurement of the K-/K+ ratio from Ni+Ni collisions at 1.91A GeV - Piasecki, Krzysztof; Herrmann, Norbert; Benabderrahmane, Mohamed Lotfi; Deppner, Ingo Martin; Pelte, Dietrich; Zinyuk, Victoria; Liu, Jian-Li (Physical review, 2019)
The FOPI Collaboration at the GSI SIS-18 synchrotron measured charged kaons from central and semicentral collisions of Ni+Ni at a beam energy of 1.91A GeV. We present the distribution of the K−/K+ ratio on the energy vs polar angle plane in the nucleon-nucleon center-of-mass frame, with and without subtraction of the contribution of ϕ(1020) meson decays to the K− yield. The acceptance of the current experiment is substantially wider compared to the previous measurement of the same colliding system. The ratio of K− to K+ energy spectra is expected to be sensitive to the in-medium modifications of basic kaon properties like mass. Recent results obtained by the HADES Collaboration at 1.23A and 1.76A GeV indicate that after inclusion of the ϕ meson decay contribution to the K− production no difference between the slopes of the K− and K+ energy spectra is observed within uncertainties. For our data a linear fit to this ratio obtained after subtraction of the ϕ meson contribution still shows a decrease with kinetic energy, although a constant value cannot be rejected. The contribution of Λ(1520)→pK− decays estimated from fitting the thermal model to the experimental yields appears to be another factor of moderate relevance.
Im Titel sind die Zeichen "plus" und "minus" hochgestellt
Gesehen am 09.05.2019